Virtual reality support during systemic cancer therapy to improve anxiety/depressive symptoms and reduce toxicity in patients with gastrointestinal cancers—OncoVR - S. Kasper; S. Liszio; K. Schorrmann; M. Gerigk; S. Jovic; O. Basu; K. Kostbade; B. Goraus; A. Elsakka; B. Puladi; J. Kleesiek; M. Schuler; et al. (ESMO Gastrointestinal Oncology)
Background: Systemic cancer therapy may trigger anxiety/depressive symptoms and toxicity. Relaxation techniques can help alleviate toxicities but their implementation in clinical practice is challenging. We hypothesize that virtual reality (VR) systems which project a relaxing nature environment may help to reduce psychological stress and toxicities of cancer therapies. This trial aims to evaluate the feasibility of a supportive VR intervention in patients receiving cancer therapies in an outpatient setting. Patients and methods: OncoVR is a randomized, open-label, cross-over trial to investigate the feasibility and impact of VR support during cancer therapy to improve anxiety, depressive symptoms, and toxicity in patients with gastrointestinal cancers. In total, 54 participants will be assigned to receive systemic therapy with VR support, followed by a subsequent course without VR support (arm A). Patients in arm B will first receive therapy without VR support, followed by a subsequent course with VR support. Primary endpoints are the feasibility of VR support (80% of the patients can tolerate its use for a minimum duration of 20 min), and changes in anxiety/depressive symptoms using the Hospital Anxiety and Depression Scale (HADS-D) and Positive and Negative Affect Schedule (PANAS) questionnaires. Secondary endpoints include the incidence and severity of therapy-associated toxicities per National Cancer Institute Common Terminology Criteria for Adverse Events (NCI-CTCAE) and Patient-Reported Outcomes version of the CTCAE (PRO-CTCAE) grading, and patient experience using the Player Experience Inventory (PXI) questionnaire.